Development of Human Resource Management in 21st Century Higher Education - Adrie Oktavio; Rahman Tanjung; Erlinawati Situmorang; Mariaty Saragih; M. Anton Fatoni (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2024)
Higher instruction within the 21st century faces complex challenges in viably overseeing human assets (HR). Energetic changes in innovation, socioeconomics, and partner desires impact how instructive institutions manage their HR to realize key goals.This consider points to distinguish best hones and techniques in HR administration inside higher instruction educate, as well as investigate the part of development and adjustment to later advancements in HR management.Qualitative approach was utilized, utilizing in-depth interviews and archive investigation to assemble information from different higher instruction educate around the world. The research sample comprised of HR pioneers and professionals experienced within the higher instruction context.The inquire about discoveries demonstrate that the improvement of HR administration in 21st century higher instruction requests approaches based on advancement, collaboration, and adjustment to alter. Compelling techniques incorporate the usage of innovation to upgrade operational proficiency, the advancement of comprehensive administration, and capacity-building to oversee HR differing qualities and complexity. This study provides bits of knowledge into how higher instruction institutions can improve their HR administration to realize competitive advantage and vital objectives within the current computerized period.